PENGARUH UKURAN PERUSAHAAN DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Tirza Andriansyah (2017)
This study was conducted to examine the effect of firm size and board commissioner size toward. This study uses bank companies listed in Indonesia Stock Exchange as a sample. Sampling technique using purposive sampling method. Selection of sample 44 banking companies listed in Indonesia Stock Exchange in 2013-2015 resulted in 35 companies that are acceptable. Testing the hypothesis in this study using Multiple Linear Regression Analysis with SPSS 21 and a significance level of 5 %. The results of the testing showed that: (1) firm size has a non-significant influence on the enterprise risk management dicloure with a significance level of 0.323 is greater than the specified level α = 0.05. (2) Board commissioner size has non-significant influence on the enterprise risk management disclosure because it has a significance level of 0.078 is greater than the specified level α = 0.05.